Questioning the (new) woman question : Rethinking and rereading late nineteenth-century antifeminist novels beyond binarised rhetoric - Wang, Esther Ying Jie (2009)
The nineteenth-century, or the Victorian period, is the age of the novel, and well known for its numerous influential authors, from Charles Dickens to Anthony Trollope. However, beyond the figures of George Eliot, the Brontë sisters, and Elizabeth Gaskell, not many female novelists of the age remain in literary consideration, or even popularly read. This paper focuses on redressing the marginalisation of the late nineteenth-century antifeminist women writers. By engaging with four selected aspects – domesticity, professional work, marriage, and religion – of conventional Victorian constructions of femininity, this paper argues the literary neglect of the conservative writers to be product of binarised and delimiting antifeminist/feminist assessments, and proves the selected novelists to have written beyond these politicized polarities, and thus, to be reconsidered for contemporary readership and reintroduction into the Victorian canon.